Studi Perilaku Tahanan Cabut (Pull - Out Resistance) Pada Tanah Berpasir - Putra, Hadiyan; Fatnanta, Ferry; Muhardi, Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Soil improvement technique was first introduced by Vidal, 1966, by using a metal strip as soil reinforcement on structure reinforced earth. Soil improvement techniques suited to reinforcement materials used in the structure of soil retaining walls, road structure, the base of the bridge, and repair slopes. Proven by use steel reinforcement, in addition to structure flexible and easy in implementation, can also reduce deformation both vertical and lateral directions. Selection is based sand graded well as the properties it owns, among tractable in employment stack, including the last ingredient, and not cohesive strength is not affected until the rate of moisture. Pull out resistance scale laboratory use plain steel reinforcement diameter 10 mm with the direction and shape of the power profile is retrofitting the longitudinal direction, transverse direction, square-shaped profile, the profile of triangular and square-shaped profile combination. Each test used optimum water content (OMC) and tensile stress normal to be used only on reinforcement overburden soil. In testing using shaped reinforcement square profiles obtained resistivity values greater pull out resitance than the pull out resistance value using directional and other forms of reinforcement profiles. Keywords: Reinforcement, pullout resistance, water content